2017
DOI: 10.1111/head.13059
|View full text |Cite
|
Sign up to set email alerts
|

Pourfour du Petit Syndrome Associated With Right Eye Pressure

Abstract: Pourfour du Petit (PDP) syndrome is a rare disorder characterized by ipsilateral mydriasis, eyelid retraction, and hemifacial hyperhidrosis caused by hyperactivity of the ipsilateral oculosympathetic pathway. A case is presented of PDP syndrome associated with likely ipsilateral occipital neuralgia. We review the causes and co-morbidities and the clinical features of PDP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 28 publications
(51 reference statements)
0
1
0
Order By: Relevance
“…The first step in our approach was to rule out a chest or neck neoplasia (particularly an apical lung mass, a paravertebral metastatic mass [ 2 ], breast cancer, neurofibroma, or thyroid adenoma), followed by a cervical rib and infections (tuberculosis, aspergillosis, and cryptococcosis [ 11 ] have been reported as causes of second-order PdPS). Next, to investigate potential known vascular etiologies, such as a thoracic aneurysm [ 12 ], we ordered chest and neck CT and MR angiography. In our angiographic studies, we found left-sided (contralateral) internal jugular vein agenesis and, as a result, right-side (ipsilateral) internal jugular vein distention that was compressing the ipsilateral sympathetic chain.…”
Section: Discussionmentioning
confidence: 99%
“…The first step in our approach was to rule out a chest or neck neoplasia (particularly an apical lung mass, a paravertebral metastatic mass [ 2 ], breast cancer, neurofibroma, or thyroid adenoma), followed by a cervical rib and infections (tuberculosis, aspergillosis, and cryptococcosis [ 11 ] have been reported as causes of second-order PdPS). Next, to investigate potential known vascular etiologies, such as a thoracic aneurysm [ 12 ], we ordered chest and neck CT and MR angiography. In our angiographic studies, we found left-sided (contralateral) internal jugular vein agenesis and, as a result, right-side (ipsilateral) internal jugular vein distention that was compressing the ipsilateral sympathetic chain.…”
Section: Discussionmentioning
confidence: 99%